Traffic Management Plan Along Roxas Avenue, Iligan City: An Academic-LGU Initiative in Urban Transport - F. FALAME, PHOEBE MAY; P. GELAGA, RHODA; L. MAGANGCONG , AMERSAB; B. PATAYON, ANNABELLE; S. RAVACIO, NESSA TIFFANY; F. RESURRECCION, PAMELA (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This study aimed to determine the business related skill and competency requirements of industries, business firms, financial and academic institutions in Iligan City. It used personal factors as parameters in determining these skills. These competencies are personal, communication, computer, organizational, entrepreneurial, internatignal/cultural and domain competencies. The descriptive method of research applying basic descriptive statistics such as frequency, percentages and proportions, mean, standard deviation and, coefficient variation was used. A structured survey questionnaire was used to gather data from 33 business organizations. Results of the study indicated that in general, industries and business firms in Iligan City today give more importance to the organizational competencies of individuals as a main requirement from their applicants and employees. In the personal competency category, integrity topped among the four factors while problem solving is the least, although all of the four factors were rated as "very important." In the communication competency category, the survey revealed that all of the six factors are very important but writing and oral communication skills as the most important among the six communication competencies while public speaking was found to be the least important in this competency category. In the computer competencies category, accuracy, which is under the encoding skills, topped as the most important while the skill in blogging, which is under the Internet subcategory, is rated as the least important. In the organizational competencies category, all factors are rated as very important though the leadership/ management skill was regarded as the most important; and, economics/statistics as the least but still indicated as very important; In the entrepreneurial competency category, only risk taking is regarded as important and the rest are indicated as very important. Demand for efficiency and quality is considered as most important among the entrepreneurial competency factors while risk taking as the least important. In the international and intercultural competencies, the data showed that cross-cultural competencies were rated as the highest. It is followed by having international knowledge, then by having knowledge in International Human Resource. Learning a second language is also rated as the fourth important factor. International marketing, international trade theory and international management were rated least important among the factors. When it came to domain competencies, having knowledge in Financies was preferred on knowledge in Accounting. Industries and business firms, therefore, in Iligan City are generally giving more importance to the organizational competencies of individuals as a main requirement from their applicants and employees. The seven skills and competency factors used in the study are regarded as important, thus, must be incorporated in any business curriculum.